2022
DOI: 10.3389/fphy.2022.769904
|View full text |Cite
|
Sign up to set email alerts
|

From Thermodynamics to Information: Landauer’s Limit and Negentropy Principle Applied to Magnetic Skyrmions

Abstract: Magnetic skyrmions are topological swirling spin textures objects that can be manipulated and employed as information carriers. This is accomplished based either on their ground-state properties or their thermodynamic properties. Landauer’s principle establishes an irreversible conversion from information to physics. The inverse mechanism, the inverse mechanism is proposed for magnetic topological defects forming in magnetic nanostructures that are regarded as closed thermodynamic systems confirming Szilard’s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 53 publications
(93 reference statements)
1
3
0
Order By: Relevance
“…the sum of probabilityweighted entropy of each configuration. Similar discussions were presented in the literature such as recently by Zivieri [117] by considering the conversion of the thermodynamic 39)), with the negentropy or 'negative entropy' corresponding to the loss of thermodynamic entropy from the magnetic skyrmion which are topological swirling spin textures of individual configurations employed as information carriers, i.e.…”
Section: Multiscale Entropy and Its Coarse-grainingsupporting
confidence: 56%
“…the sum of probabilityweighted entropy of each configuration. Similar discussions were presented in the literature such as recently by Zivieri [117] by considering the conversion of the thermodynamic 39)), with the negentropy or 'negative entropy' corresponding to the loss of thermodynamic entropy from the magnetic skyrmion which are topological swirling spin textures of individual configurations employed as information carriers, i.e.…”
Section: Multiscale Entropy and Its Coarse-grainingsupporting
confidence: 56%
“…They are typically a few nanometers in diameter and can be found in several magnetic materials due to competing Heisenberg exchange and Dzyaloshinskii-Moriya interactions (DMI). These stable structures are essential choices for storing information in upcoming technological devices [1][2][3][4][5][6][7][8][9][10][11][12]. Application of an electric current may record, read and erase skyrmions [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Application of an electric current may record, read and erase skyrmions [13][14][15]. Additionally, coding information based on the information entropy may be employed in prospect for improving data transmission [12].…”
Section: Introductionmentioning
confidence: 99%
“…A bit of information is obtained by the demon at the price of some negative entropy lost in the environment, which allows the demon to make choices which decrease the entropy in the environment. The relation between the negentropy and the Landauer limit was analyzed in [8,9] considering a system of magnetic skyrmions. There, it was shown that the Landauer bound can be seen as a variation of the negentropy of the skyrmion.…”
Section: Introductionmentioning
confidence: 99%